1991
DOI: 10.1139/z91-405
|View full text |Cite
|
Sign up to set email alerts
|

The eggs of Forficula auricularia L. (Dermaptera, Forficulidae): ultrastructure and resistance to low and high temperatures

Abstract: The morphology, ultrastructure, and resistance to low and high temperatures of the fertilized egg of Forficula auricularia were studied both before and after water absorption. The increase in volume resulting from water absorption did not modify the ultrastructure of the envelopes. The chorion was found to be made of five distinct layers and of a vitelline envelope under which a serosal cuticle was secreted by the embryo. Before hydration, the supercooling point of the egg was −27 °C; after hydration, it was −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…We showed that mothers transfer hydrocarbons to the egg surface, and it is well known that hydrocarbons on the cuticle of insects are key for water homeostasis (Blomquist and Bagnères 2010). Thus, the low quantities of hydrocarbons on the unattended eggs ( Figure 4B,C) might have facilitated passive water absorption by the embryos from the substrate and surrounding air leading to their heavier fresh weight at hatching (Chauvin et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that mothers transfer hydrocarbons to the egg surface, and it is well known that hydrocarbons on the cuticle of insects are key for water homeostasis (Blomquist and Bagnères 2010). Thus, the low quantities of hydrocarbons on the unattended eggs ( Figure 4B,C) might have facilitated passive water absorption by the embryos from the substrate and surrounding air leading to their heavier fresh weight at hatching (Chauvin et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…When no hydropyles are present, water is absorbed through the entire surface of the egg (Larink and Balinski 1989;Chauvin et al 1991). In contrast, in O. olens, there are about 4000 chorionic hydropyles (aeropyles) throughout the outer layer of the chorion in an equatorial band around the egg (Lincoln 1961).…”
Section: Discussionmentioning
confidence: 99%
“…Hydropic eggs require absorption of water from their environment to complete their development (Hinton 1981;Chauvin et al 1991). Such eggs are found in many aquatic and terrestrial insect species of Orthoptera, Hemiptera, Homoptera, Hymenoptera, Diptera and Coleoptera (Hinton 1981).…”
Section: A Introductionmentioning
confidence: 99%
See 1 more Smart Citation